If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -5) = 5(2x + -1) Reorder the terms: 3(-5 + 4x) = 5(2x + -1) (-5 * 3 + 4x * 3) = 5(2x + -1) (-15 + 12x) = 5(2x + -1) Reorder the terms: -15 + 12x = 5(-1 + 2x) -15 + 12x = (-1 * 5 + 2x * 5) -15 + 12x = (-5 + 10x) Solving -15 + 12x = -5 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -15 + 12x + -10x = -5 + 10x + -10x Combine like terms: 12x + -10x = 2x -15 + 2x = -5 + 10x + -10x Combine like terms: 10x + -10x = 0 -15 + 2x = -5 + 0 -15 + 2x = -5 Add '15' to each side of the equation. -15 + 15 + 2x = -5 + 15 Combine like terms: -15 + 15 = 0 0 + 2x = -5 + 15 2x = -5 + 15 Combine like terms: -5 + 15 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| x=-14+5y | | 5-x+37=50-10 | | 3a+6=-4a+2 | | 12x-21=28(4x-1) | | 12y^9/2y^11 | | 5-9/8x=6 | | X-4+4=-7 | | (y^2-x^2)dy+(2*x*y)dx=0 | | X-4+4=7 | | F(x)=-3(x+3)squared+3 | | 4+16x=10+15x | | 8x+-7=-2x+5 | | 10+3x-x-4=x | | 13x+17+34=90 | | 8x+1+9x-7=180 | | Z-6=z-4 | | -2x-7=32 | | (4+8)n=36 | | (4+8)n=3 | | 10x-14=-2x-13 | | 772x= | | 10x-14=2x+13 | | 5y+39+4x+6=180 | | x(x+2)=1295 | | 9x-15=-5x-16 | | 9x-15=5x+16 | | n-8+3=5 | | 8x+2=4(6x-9) | | 26=2x-8+4x | | 8x+2=4-(6x-9) | | .6(X+100)+.8X=109 | | 104=2x+2(x+4) |